Evolution of the Tim17 protein family - Žárský, Vojtěch; Doležal, Pavel (Biology direct, 2016)
BACKGROUND: The Tim17 family of proteins plays a fundamental role in the biogenesis of mitochondria. Three Tim17 family proteins, Tim17, Tim22, and Tim23, are the central components of the widely conserved multi-subunit protein translocases, TIM23 and TIM22, which mediate protein transport across and into the inner mitochondrial membrane, respectively. In addition, several Tim17 family proteins occupy the inner and outer membranes of plastids. RESULTS: We have performed comprehensive sequence analyses on 5631 proteomes from all domains of life deposited in the Uniprot database. The analyses showed that the Tim17 family of proteins is much more diverse than previously thought and involves at least ten functionally and phylogenetically distinct groups of proteins. As previously shown, mitochondrial inner membrane accommodates prototypical Tim17, Tim22 and Tim23 and two Tim17 proteins, TIMMDC1 and NDUFA11, which participate in the assembly of complex I of the respiratory chain. In addition, we have identified Romo1/Mgr2 as Tim17 family member. The protein has been shown to control lateral release of substrates fromTIM23 complex in yeast and to participate in the production of reactive oxygen species in mammalian cells. Two peroxisomal proteins, Pmp24 and Tmem135, of so far unknown function also belong to Tim17 protein family. Additionally, a new group of Tim17 family proteins carrying a C-terminal coiled-coil domain has been identified predominantly in fungi. CONCLUSIONS: We have mapped the distribution of Tim17 family members in the eukaryotic supergroups and found that the mitochondrial Tim17, Tim22 and Tim23 proteins, as well as the peroxisomal Tim17 family proteins, were all likely to be present in the last eukaryotic common ancestor (LECA). Thus, kinetoplastid mitochondria previously identified as carrying a single Tim17protein family homologue are likely to be the outcome of a secondary reduction. The eukaryotic cell has modified mitochondrial Tim17 family proteins to mediate different functions in multiple cellular compartments including mitochondria, plastids and peroxisomes. Concerning the origin of Tim17 protein family, our analyses do not support the affiliation of the protein family and the component of bacterial amino acid permease. Thus, it is likely that Tim17 protein family is exclusive to eukaryotes. REVIEWERS: The article was reviewed by Michael Gray, Martijn Huynen and Kira Makarova.
Keywords: Mitochondria; Peroxisome; molekulární evoluce; transportní proteiny mitochondriální membrány; sekvenční seřazení; Tim17; Plastid; Evolution; Phylogeny; TIMMDC1; Evolution, Molecular; sekvence aminokyselin; Tim22; Pmp24; Protein import; NDUFA11; Amino Acid Sequence; Romo1; fylogeneze; Mitochondrial Membrane Transport Proteins; Oep16; Tim23; Tmem135; Sequence Alignment